THE EFFECT OF VARIATIONS IN ROASTING TEMPERATURE ON YIELD AND PERCENTAGE OF INHIBITION OF DPPH RADICAL REDUCTION IN CANDLENUT OIL THE UV-Vis SPECTROPHOTOMETRIC METHOD - Aldi Budi Riyanta; Maulani Fitrie Nabila; Akhmad Aniq Barlian (Jurnal Farmasi Sains dan Praktis, 2021)
Antioxidant compounds are able to dampen free radicals by donating electrons to pair with free radicals and become harmless to the body. One of the plants that can be used as an antioxidant is candlenut. Candlenut (Aleurites moluccana (L.) Willd.) Candlenut is a plant that has many benefits. Chemical content contained in candlenut seeds is such as flavonoids have the ability as antioxidants. This research aims to determine the roasting temperature of yield and inhibition percentage of DPPH radical reduction (1,1-diphenyl-2-picylhydrazyl) contained in candlenut oil using the UV-Vis spectrophotometric method. The variations in roasting temperature used were 30, 70, 75, 80, 85, and 90˚C. The yield obtained from the extraction was 42,12 %, 38,47 %, 36,44%, 32,58 %, 31,06 %, and 25,38 % which indicated that the higher the roasting temperature the lower the yield obtained. While the percentage of DPPH radical reduction showed a value of 24,689±0,23%; 27,399±0,02%; 38,464±0,01%; 44,562±0,04%; 37,222±0,03% and 22,657±0,03% which shows that 80°C is the best temperature to produce the biggest DPPH radical scavenging.